Excess mortality and years of life lost from 2020 to 2023 in France: a cohort study of the overall impact of the COVID-19 pandemic on mortality - Gilles Hejblum; Nathanael Lapidus; Paul Moulaire (BMJ Public Health, 2025)
Introduction Excess mortality has been frequently used worldwide for summarising the COVID-19 pandemic-related burden. Estimates for France for the years 2020–2022 vary substantially from one report to another, and the year 2023 is poorly documented. The present study assessed the level of excess mortality that occurred in France between 2020 and 2023 together with the corresponding years of life lost (YLL), in order to provide a reliable, detailed and comprehensive description of the overall impact of the pandemic.Method This open cohort study of the whole French population analysed the 8 451 372 death occurrences reported for the years 2010–2023. A Poisson regression model was trained with years 2010–2019 for determining the age-specific and sex-specific evolution trends of mortality before the pandemic period. These trends were then used for estimating the excess mortality during the pandemic period (years 2020–2023). The life expectancies of the persons in excess mortality were used for estimating the corresponding YLL.Results From 2020 to 2023, the number of excess deaths (mean (95% CI) (percentage of change versus expected mortality)) was, respectively, 49 541 (48 467; 50 616) (+8.0%), 42 667 (41 410; 43 909) (+6.9%), 53 129 (51 696; 54 551) (+8.5%), and 17 355 (15 760; 18 917) (+2.8%). Corresponding YLL were 512 753 (496 029; 529 633), 583 580 (564 137; 602 747), 663 588 (641 863; 685 723), and 312 133 (288 051; 335 929). Individuals younger than 60 years old accounted for 17% of the YLL in 2020, 26% in 2021, 32% in 2022 and 50% in 2023. Men were more affected than women by both excess mortality and YLL.Conclusion This study highlights the long-lasting impact of the pandemic on mortality in France, with four consecutive years of excess mortality and a growing impact on people under 60, particularly men, suggesting lasting and profound disruption to the healthcare system.